Wealth Shocks and Health Outcomes: Evidence from Stock Market Fluctuations - Hannes Schwandt (Institute for the Study of Labor (IZA), 2014)
Do wealth shocks affect the health of the elderly in developed countries? The economic literature is skeptical about such effects which have so far only been found for poor retirees in poor countries. In this paper I show that wealth shocks also matter for the health of wealthy retirees in the US. I exploit the booms and busts in the US stock market as a natural experiment that generated considerable gains and losses in the wealth of stock-holding retirees. Using data from the Health and Retirement Study I construct wealth shocks as the interaction of stock holdings with stock market changes. These constructed wealth shocks are highly predictive of changes in reported wealth. And they strongly affect health outcomes. A 10% wealth shock leads to an improvement of 2-3% of a standard deviation in physical health, mental health and survival rates. Effects are heterogeneous across physical health conditions, with most pronounced effects for the incidence of high blood pressure, smaller effects for heart problems and no effects for arthritis, diabetes, lung diseases and cancer. The comparison with the cross-sectional relationship of wealth and health suggests that the estimated effects of wealth shocks are larger than the long-run wealth elasticity of health.
Keywords: G10; I10; J14; 330; retiree health; wealth shocks; stock market